Isolated limb perfusion for the management limb threatening soft tissue sarcomas: The role of histological type on clinical outcomes. Issue 2 (February 2017) - Rastrelli, M.; Mocellin, S.; Stramare, R.; Brunello, A.; Maruzzo, M.; Basso, U.; Scarzello, G.; Buzzaccarini, M.S.; Pilati, P.; Saadeh, L.M.; Del Fiore, S.P.; Tosi, A.; et al.
Abstract: Background: Hyperthermic isolated limb perfusion (HILP) is an effective neoadjuvant treatment to avoid amputation in patients with locally advanced extremity soft tissue sarcomas (STS). We aimed to investigate whether STS histological type plays a role in predicting clinical outcomes. Methods: This study reports a retrospective analysis of 125 patients with limb threatening STS (liposarcoma, n = 41; malignant peripheral nerve sheath tumor, n = 20; leiomyosarcoma, n = 20; miscellany, n = 44), who underwent HILP from 1990 through 2015 at our institution. The following endpoints were evaluated: tumor response (assessed by radiological imaging and histology), limb sparing rate, local progression-free survival (LPFS) and overall survival (OS). Results: On average, overall (complete + partial) tumor response was significantly greater in patients affected with liposarcoma as compared to those with other histotypes (radiological response rate: 38/41, 92.7% vs 66/84, 78.6%, P-value: 0.048; mean histological necrosis: 83.6% vs 52.9%, P < 0.0001). Limb sparing rate was also higher among patients with liposarcoma as compared to other histotypes (39/41, 95.1% vs 62/84, 73.8%, P-value: 0.005). As regards survival, LPFS was similar across tumor types, whereas OS resulted significantly worse in patients with limb leiomyosarcoma (log-rank P-value: 0.009). Conclusions: HILP is a very effective treatment modality for limb threatening STS. In our series, liposarcoma appears to be the histological type most sensitive to HILP in terms of tumor response and thus limb sparing, which might help clinicians in the patient selection process.